Charles Anderson Wickliffe, The Revised Statutes of Kentucky, Approved and Adopted by the General Assembly, 1851 and 1852: in Force from July 1, 1852 Page 671, Image 679 (1852) - (:unkn) unknown (General Publisher, 1852)
No person, except a gunsmith on his own premises, shall shoot off a gun or pistol in a town. Any person offending herein shall be fined five dollars and costs, to be collected by the trustees, and applied to keeping the streets of the town in repair.
--
Keywords: DISCHARGE